Repetitive shock vibration risk assessment for gunshots - Marchetti, Enrico; Di Giovanni, Raoul; Tirabasso, Angelo; Lunghi, Alessandro; Morgia, Federica (Canadian Acoustics, 2011)
Processing measures of typical shock vibration such as those of firearms was conducted with the help of ISO/TS 15694:2004 standard. Triaxial acceleration on the butt of three Beretta firearms were measured with an accelerometer mounted in an adaptor. Analysis and processing was done with MatLab software and the processing rms and root mean quad (rmq) parameters were proposed with a computation time window of either 3 or 30 seconds. Firing with firearms, as it is expected from impulsive events, encompasses a far larger frequency range than usual vibration exposure. The results show widening the time window reduces the indicator value. The effect of the fourth power (rmq) is not that of enhancing the exposure assessment, instead it depresses it. This can be attributed to the impulsive shot and its very short time duration, which implies a wide spectrum in frequency domain and acceleration values below 1m/s2 in low frequency bands.